Validation of the Pregnancy Physical Activity Questionnaire (PPAQ) - Suliga, Edyta; Sobaś, Kamila; Król, Grzegorz (Medical Studies/Studia Medyczne, 2017)
Introduction : The results of many studies confirm the positive effect of physical activity during pregnancy on the health of both mother and child. Due to this, it is important to use standardised methods of its assessment. In 2004, Chasan-Taber et al. developed the Pregnancy Physical Activity Questionnaire (PPAQ), taking into account household/caregiving activities, occupational activities, sports/exercise activities, transportation activities, and inactivity. Aim of the research : The validation of the Pregnancy Physical Activity Questionnaire (PPAQ) by determination of its reproducibility. Material and methods : The questionnaire was validated from June 2014 to February 2015 among 164 women. The respondents were surveyed twice in a 2-week interval. The repeatability of the questionnaire was verified by determining the Pearson correlation coefficient between the results obtained for the same people in the first and second interview, thus determining the intra-subject variability. Inter-subject variability was analysed by comparing the average values of physical activity for the whole group using the Student’s t-test for dependent samples. Results : For all levels of physical activity, a high correlation between the results obtained in both interviews was found. The correlation coefficient for total physical activity was r = 0.96. The reproducibility of the results obtained from PPAQ questionnaire was the highest for inactivity and moderate activity (r = 0.96). The analysis according to the type of activity showed that the reproducibility was the highest for occupational activity (r = 0.98). Conclusions : High reproducibility of results obtained using PPAQ questionnaire was found. This allows the assessed questionnaire to be considered as an accurate measurement tool that can be a source of reliable information about physical activity in pregnant women.